Construções históricas da Ilha de Villegagnon - Tenente Ricardo dos Santos Guimarães (Navigator)
The present work is an invitation to the reader interested in knowing a little more about the history of the small island on which, during the sixteenth century, Nicolas Durand de Villegagnon adventured to establish a French colony. Situated in a strategic location, at the entrance to Guanabara Bay, various transformations have taken place during the four hundred and fifty years of occupation since Fort Coligny was established, from the arrival of Villegagnon, in 1555, to the construction of the present-day installations at the Naval School.